Didáctica universitaria híbrida: identidad digital creativa y multimodalidad (Altre Modernità, 2022)
The incipient interest in hybrid and collaborative didactics in times of COVID-19 highlights the fundamental role of digital hybrids in the training of university students. New mobile devices allow the ubiquity of teaching-learning processes. But they not only allow the possibility of sharing and communicating at any time and place. In these devices, different tools that integrate different representation systems converge, and offer new forms of construction, representation and communication of knowledge. From the questioning of the hegemonic technological culture, and from a didactic approach that advocates comprehensive and critical teaching, we want to present the creative functions of mobile devices so that students can build their own texts, new multimodal narratives, for the construction of a creative digital identity. An identity that allows them to perceive, analyse, reflect, produce, communicate and participate in their environment in a collaborative way. We present a transgressive didactic proposal based on photographic narration that displays new semiotic ways of building knowledge and making it known. We discuss its value to rethink other functions of academic knowledge and assessment, beyond achievement tests, critical dimensions in the University.